The design and implementation of a distributed data capture and processing framework for ground penetrating radar - Wallis, Allen Bruce (Department of Electrical Engineering, 2014)
This dissertation describes the development of a distributed data-capture and data-processing framework for use with a network-aware ground penetrating radar. The software that was developed addresses weakness in existingg data processing software, with the main focus being on the distributed capabilities of the framework.